Measurement of hydrogen and embrittlement of high strength steels. (January 2016) - Sanchez, J.; Lee, S.F.; Martin-Rengel, M.A.; Fullea, J.; Andrade, C.; Ruiz-Hervías, J.
Abstract: Hydrogen embrittlement of high strength steel is believed to be one of the main reasons for the cracking of prestressed concrete structures. In this study, hydrogen was generated on the steel surface by applying different fixed cathodic potentials. The steel was immersed in simulated carbonated concrete solutions with and without 0.1 M NaCl. Simultaneously, the steel was subjected to tensile loading at slow strain rate until fracture. Fractographic analysis and the measurement of the concentration of absorbed hydrogen in the iron lattice were performed. Results showed that the hydrogen atom only penetrated into the iron lattice when the steel was loaded above its yield stress. This phenomenon produced quasi-cleavage like fracture, and the strain at fracture was considerably reduced. The presence of chloride ion together with the hydrogen embrittlement did not provoke a remarkable synergic effect in the mechanical properties of high-strength steel. Highlights: Hydrogen only penetrated into the iron lattice when it is loaded above yield stress. Hydrogen reduced cohesive energy and it induces a quasi-cleavage fracture. The presence of chloride ion with the HE didn't provoke a remarkable synergic effect. Cathodic protection can be suitable in aggressive media to avoid corrosion or SCC. It is given a phenomenological law for HE in function of hydrogen content.